2022
DOI: 10.3390/ijerph191811542
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Concurrent Training Combined with Low-Carbohydrate High-Fat Ketogenic Diet on Body Composition and Aerobic Performance: A Systematic Review and Meta-Analysis

Abstract: (1) Background: Recently, studies have emerged to explore the effects of concurrent training (CT) with a low-carb, high-fat ketogenic diet (LCHF) on body composition and aerobic performance and observed its benefits. However, a large variance in the study design and observations is presented, which needs to be comprehensively assessed. We here thus completed a systematic review and meta-analysis to characterize the effects of the intervention combining CT and LCHF on body composition and aerobic capacity in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…If the selected meta-analyses are reviewed in terms of caloric intake [11,24,26,29,31,32,34,44,57], several observations can be made. When we further examined the data from the six included publications in Gohari et al's meta-analysis [29], we found that information on caloric intake was either completely missing [59] or that the ketogenic and control groups consumed different amounts of calories [60].…”
Section: Lower Caloric Intake In the Ketogenic Diet Group Than In The...mentioning
confidence: 99%
See 2 more Smart Citations
“…If the selected meta-analyses are reviewed in terms of caloric intake [11,24,26,29,31,32,34,44,57], several observations can be made. When we further examined the data from the six included publications in Gohari et al's meta-analysis [29], we found that information on caloric intake was either completely missing [59] or that the ketogenic and control groups consumed different amounts of calories [60].…”
Section: Lower Caloric Intake In the Ketogenic Diet Group Than In The...mentioning
confidence: 99%
“…In the case of Wang et al's meta-analysis [34], two of the included publications [61,62] prescribed more calories for the ketogenic group than for the control group.…”
Section: Lower Caloric Intake In the Ketogenic Diet Group Than In The...mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding exercise performance, the most recent systematic reviews, including or not meta-analysis, showed that the ketogenic diet does not produce better effects compared with carbohydrate-based diets in both aerobic (e.g. cycling and running) and strength performances [7 ▪ ,9] and seems to have no effect in improving endurance performance even when combined with concurrent training [8].…”
Section: Exercise Performancementioning
confidence: 99%
“…Over the decades, several studies have been conducted about the effects of the ketogenic diet on exercise performance in different modalities and exercise modes, and on the body composition in diverse populations. Concerning this issue, there were several studies with meta-analyses published recently [7 ▪ ,8–10]. They all showed no advantage of the ketogenic diet over normal/high carbohydrate-based diets on physical performance.…”
Section: Introductionmentioning
confidence: 99%